2023
DOI: 10.1002/slct.202300592
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Isotherm and Kinetic Modeling of the Congo Red (CR) and Indigo Carmine (IC) Dyes Removal onto Novel Bentonite Hybrid Material

Abstract: The present study focuses on investigating the adsorption characteristics of anionic Congo Red (CR) and Indigo Carmine (IC) dyes using hexadecyltrimethyl ammonium bromide‐modified Bentonite (HDTMA‐Bentonite) with varying loading amounts. The removal effectiveness of anionic dyes was examined as a function of the HDTMA+ loaded amount, contact time, initial concentration, and adsorbent dosage. The XRD data revealed that the interlayer spacing of Bentonite increased from 1.42 to 1.98 nm. The FTIR approach was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…In previous studies, [66–74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, [66–74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Resultsmentioning
confidence: 99%